Socialization of Provision of Internship II for English Students at the University of Prof. Dr. Hazairin SH - Yosi Marita; Elva Utami (CV Media Inti Teknologi, 2022)
This socialization aims to provide provision for English students who will take part in the second internship program at school. The socialization and debriefing will be held on Monday 17 October 2022 in the C4 learning building at 08.00-14.00 WIB. The participants for apprentice II were all semester V students. Implementation of socialization and debriefing of apprentice II program for English students at Prof. Dr. Hazairin SH through the lecture method. Internship Program IIaims to strengthen educational academic competence and linkageswith academic competence in the field of study as well as determining the initial abilities of prospective teachers in developing learning tools through: reviewing the curriculum and learning tools used by teachers, reviewing learning strategies, reviewing evaluation systems, compiling and developing Learning Implementation Plans (RPP), developing learning media, developing teaching materials in accordance with the lesson plans; and development of evaluation tools in accordance with the objectives. Implementation of socialization and debriefing of apprentice program II for English students at the University of Prof. Dr. Hazairin SH makes students able to design learning tools, namely studying the curriculum, designing syllabus, and designing learning plans as well as being able to know the school environment carefully.